Case report: A rare appearance of preretinal deposits in a patient with uveitis: multimodal imaging observation - Cheng, Yizhe; Chen, Chunli; Xiao, Yuanyuan; Wang, Shuang; Wang, Sihui; Peng, Xiaoyan (Frontiers in Medicine, 2023)
Background: Uveitis is a disease presenting with varied clinical symptoms and potentially devastate visual function. Here we report a patient with uveitis exhibiting a rare appearance of preretinal deposits (PD).Case presentation: A 49-year-old female showed vitreous opacity and perivascular white PD involving both veins and arteries. The interferon-gamma release assay was strongly positive, chest computed tomography showed clues of calcified nodules, and other tests were unremarkable. The patient was diagnosed with uveitis and tubercular infection. The patient was given systemic antitubercular therapy and steroid, then combined with immunosuppressants. The shrinkage of HRD was more sensitively observed on OCT than on photographs during follow-up visits. The right eye was relieved subsequently, but the left showed vitreous opacity and had a poor response to the treatment. Three months after the dexamethasone intravitreal implant, the perivascular deposits in the left eye disappeared and vitreous opacity was relieved.PDs could appear as spotted deposits in the posterior pole and segmental deposits in the periphery in patients with uveitis which mainly involved the vitreous cavity, easily confused with retinal vasculitis. OCT can be more sensitive to observing the response than other examinations.